Building Islamic Ukhuwah Towards True People Establish Graceand Break Fast With The Faculty Of Law With Regional Leaders Muhammadiyah North Maluku - Saiful Hi. Soleman; Buhar Hamja (International Journal Of Community Service, 2022)
Ukhuwah means a brotherly relationship between one Muslim and another Muslim. Allah SWT. always give gifts in the form of love, brotherhood, glory, and mutual trust between fellow Muslims or towards brothers and sisters in faith. The above hadith makes it clear to us that as Muslims we are all brothers. Therefore, we as Muslims should love each other and not hurt each other. We must support each other and invite kindness to maintain ukhuwah Islamiyah, so that friendship is maintained in personality towards true human beings. . Strengthening ties of friendship in building Ukhuwah Islamiyah Towards True People.